Sex Differences in Risk for Developing Major Adverse Cardiovascular Events One Year after Hospital Discharge in Patients with Acute Coronary Syndrome - Dansuwan, Chutiporn; Phonphet, Chennet; Suwanno, Jom Suwanno (Health Science Journal of Thailand, 2022)
This study aimed to compare the differences in risks for developing MACE one year after hospital discharge between female and male patients with Acute Coronary Syndrome (ACS). Data for this secondary data analysis were obtained from 187 patients in a secondary hospital. MACE was measured by the GRACE risk score. Chi-square tests, Fisher’s exact tests and binary logistic regression were used to examine associations between the variables. The results showed that women had a higher average GRACE risk score and high-risk level than males (p-value = 0.001, 0.004, respectively). Moreover, the significant factors associated with one year mortality included age (≥80 years old) (Adjusted OR = 5.38, 95%CI: 1.40-20.69) and elevated cardiac enzymes (Adjusted OR = 5.04, 95%CI: 1.03-24.47). When classified by sex, the significant association between age and one year mortality was found only in males (Adjusted OR = 8.56, 95%CI: 1.57-46.56). The results of this study indicated that age play a crucial factor in developing MACE in patients with ACS. Healthcare providers should focus on providing care to patients with ACS aged ≥80 years, with elevated cardiac enzymes and/or a history of heart failure.